Heterogeneity in life-duration preferences: Are risky recreationists really more risk loving? - Riddel, Mary; Kolstoe, Sonja (Journal of risk and uncertainty, 2013)
We conduct multiple price list experiments that elicit life duration risk preferences from amateur auto racers, technical rock climbers, SCUBA divers, and a student control group. We posit a preference function that allows for risk aversion and probability weighting. We are particularly interested in whether the behavior of risk takers, such as risky recreationists or smokers, is best explained by a risk-tolerant utility function or if immunity to possibility bias arising from overweighting of low probabilities is a more important motivator of the choice to engage in risky activities. We find that amateur auto racers are more rational than either students or other risky recreationists because they are less likely to overemphasize low-probability events. Women, older subjects, and rock climbers are more susceptible to possibility bias than others, making them likely to overinvest in disease treatments that have a low probability of success.